Analysis of administrative-pharmaceutical completeness on patient prescriptions at Puskesmas X, Sorong City - Carmel Josuhua Paulus; Lukman Hardia; Angga Bayu Budiyanto (Institute of Computer Science (IOCS), 2026)
Prescription completeness is an important indicator in pharmaceutical services because it is related to therapeutic accuracy and patient safety. Incomplete prescriptions may increase the risk of medication errors during drug preparation and administration. This study aimed to determine the level of administrative and pharmaceutical completeness of patient prescriptions at Puskesmas X, Sorong City. This research used a descriptive observational method with a retrospective approach involving 1,572 patient prescriptions selected using a total sampling technique. The assessment was conducted based on the standards of the Indonesian Ministry of Health Regulation Number 73 of 2016 and Number 58 of 2014. The results showed that all prescriptions (100%) were categorized as incomplete. In the administrative aspect, patient name and prescription date reached 100% completeness, while patient height, doctor’s practice license number, and doctor’s phone number showed 0% completeness. Doctor’s initials/signature were found in 60.8% of prescriptions. In the pharmaceutical aspect, drug name, stability, and compatibility reached 100% completeness, while dosage form and drug strength reached 70.6% and 69.3%, respectively. The study concluded that pharmaceutical completeness was better than administrative completeness; however, prescription writing at Puskesmas X, Sorong Citis still, did not meet pharmaceutical service standards.